Atmospheric Particle Size Distributions in the Spanish Network of Environmental DMAs (REDMAAS). (November 2015) - Alonso-Blanco, E; Gómez-Moreno, F J; Artíñano, B; Samitier, S Iglesias; Juncal, V; Iglesias, M Piñeiro; Mahía, P López; Pérez, N; Brines, M; Alastuey, A; Querol, X; de la Morena, B A; et al.
Abstract: The present work is a first approach to the study of the spatio-temporal variability of the submicrometer atmospheric aerosol in Spain. The aerosol measurements have been obtained simultaneously at seven monitoring stations that compose the REDMAAS network during two measurement campaigns corresponding to summer and winter seasons. In both summer and winter periods those measurement stations with a direct influence of anthropogenic emissions recorded the highest concentrations of particle number. In the summer campaign, the average daily pattern of the aerosol size distribution in the traffic and background urban stations was conditioned by the traffic emissions and secondary aerosol formation through photochemical reactions (new particle formation events, NPF). However, the secondary aerosol had a higher contribution to the aerosol total number concentration in the rural background and high-altitude stations. In the winter campaign, in all sampling sites with the exception of Izaña station, the traffic and domestic activity emissions had a greater contribution than secondary aerosol formation on particle number total concentration. New particle formation events were identified at all sites during the summer period, and at sites without direct influence of anthropogenic emissions during the winter campaign. Some aerosol shrinkage processes were also observed at the Madrid and El Arenosillo stations.